Sistem Pendukung Keputusan Penyesuaian Nutrisi Makanan Berdasar Rekam Medis Pasien Berbasis Forward Chaining - Setiawan, Aries; Setijaningsih, Retno Astuti; Ratnawati, Juli; Agiwahyuanto, Faik; Farida, Ida; Ashari, Ayu; Prasetya, Jaka (Jurusan Teknologi Informasi Universitas Semarang, 2024)
Fulfilling nutrition for patients certainly does not only pay attention to the last illness they suffered, but nutritionists also need to pay attention to the patient's medical history. Providing certain foods to support the body's recovery after treatment for certain diseases may not necessarily be in accordance with the history of previous illnesses. Fulfilling nutritional intake according to certain disease conditions is not easy, especially if the patient has a medical history with a variety of diseases, so nutritionists need to be more selective in providing nutritional intake from a number of alternative foods that will be provided. A management decision system based on artificial intelligence is able to choose a food balance that is balanced with the various complaints experienced by patients. The method used in the food management information system for medical records uses the forward chaining method, namely by determining forward, in this case, food nutritional information that is suitable for the patient, by reading the facts that have been arranged as a representation to produce a conclusion. The accuracy value resulting from comparing manual nutrient selection and using forward chaining was 86%